PLGA nanoparticles for the oral delivery of nuciferine: preparation, physicochemical characterization and in vitro/in vivo studies. (1st January 2017) - Liu, Ying; Wu, Xin; Mi, Yushuai; Zhang, Bimeng; Gu, Shengying; Liu, Gaolin; Li, Xiaoyu
Abstract: This article reports a promising approach to enhance the oral delivery of nuciferine (NUC), improve its aqueous solubility and bioavailability, and allow its controlled release as well as inhibiting lipid accumulation. NUC-loaded poly lactic-co-glycolic acid nanoparticles (NUC-PLGA-NPs) were prepared according to a solid/oil/water (s/o/w) emulsion technique due to the water-insolubility of NUC. PLGA exhibited excellent loading capacity for NUC with adjustable dosing ratios. The drug loading and encapsulation efficiency of optimized formulation were 8.89 ± 0.71 and 88.54 ± 7.08%, respectively. NUC-PLGA-NPs exhibited a spherical morphology with average size of 150.83 ± 5.72 nm and negative charge of −22.73 ± 1.63 mV, which are suitable for oral administration. A sustained NUC released from NUC-PLGA-NPs with an initial exponential release owing to the surface associated drug followed by a slower release of NUC, which was entrapped in the core. In addition, ∼77 ± 6.67% was released in simulating intestinal juice, while only about 45.95 ± 5.2% in simulating gastric juice. NUC-PLGA-NPs are more efficient against oleic acid (OA)-induced hepatic steatosis in HepG2 cells when compared to naked NUC (n-NUC, * p < 0.05). The oral bioavailability of NUC-PLGA-NPs group was significantly higher ( **p < 0.01) and a significantly decreased serum levels of total cholesterol (TC), triglycerides (TG) and low-density lipoprotein cholesterol (LDL-C), as well as a higher concentration of high-density lipoprotein cholesterol (HDL-C) was observed, compared with that of n-NUC treated group. These findings suggest that NUC-PLGA-NPs hold great promise for sustained and controlled drug delivery with improved bioavailability to alleviating lipogenesis.